# 18t-3=3(6t-1)

## Simple and best practice solution for 18t-3=3(6t-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 18t-3=3(6t-1) equation:

Simplifying
18t + -3 = 3(6t + -1)

Reorder the terms:
-3 + 18t = 3(6t + -1)

Reorder the terms:
-3 + 18t = 3(-1 + 6t)
-3 + 18t = (-1 * 3 + 6t * 3)
-3 + 18t = (-3 + 18t)

Add '3' to each side of the equation.
-3 + 3 + 18t = -3 + 3 + 18t

Combine like terms: -3 + 3 = 0
0 + 18t = -3 + 3 + 18t
18t = -3 + 3 + 18t

Combine like terms: -3 + 3 = 0
18t = 0 + 18t
18t = 18t

Add '-18t' to each side of the equation.
18t + -18t = 18t + -18t

Combine like terms: 18t + -18t = 0
0 = 18t + -18t

Combine like terms: 18t + -18t = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.`